Prisoner-of-war ship models made in Britain: History, manufacture, materials, and treatment. Issue 1 (3rd April 2018) - Coughlin, Mary
ABSTRACT: Prisoners-of-war captured by the British during the French Revolutionary Wars (1792–1802) and the Napoleonic Wars (1803–1815) often worked assembly line style using scrap materials and leftover rations to make ship models that were sold at British markets. Since these models were created based on prisoners' memories rather than using plans, they often have inaccuracies. Despite this, prisoner-of-war ship models are considered to be some of the best records of maritime vessels from England and France during these war years. Many of the models were made of wood but the most prized models were made of bone. The description of a bone model of the HMS Caesar in the collection of the Smithsonian's National Museum of American History is presented in the context of materials typically used on such models. Research, comparison of other bone models, and Fourier transform infrared spectroscopy analysis provided insight into the history, manufacture, and materials of these models. The rigging repair on another prisoner-of-war model in the collection, a wooden model of Le Vengeur, is outlined.